Improving the methodological support of management accounting systems and control costs in dairy cattle (Journal of Economic Research & Business Administration, 2018)
The development of market relations in the agro-industrial complex of Kazakhstan, with its multistructureeconomy, should be ensured by the use of new methods of managing agricultural production.Agricultural production is a complex system that requires an appropriate scientific organization and fullfledgedmanagement. Specificity of agricultural production and management features of enterprises ofthe agro-industrial complex (AIC) in the context of the State program for the development of agriculturenecessitate the improvement of accounting and control of costs to ensure financial stability and investmentattractiveness of AIC’s enterprises.The main task of management accounting of the process of agricultural production is to scientificallysubstantiate the formation of individual costs of the agricultural organization for specific productionfacilities and determine its cost. In this regard, the purpose of the researching is to develop proposals toimprove the accounting of cost formation and the calculation of the cost of dairy products. The methodologyof the research is based on the studying of the methodology of management accounting and costcontrol in the process of calculating the cost of agricultural products.In this work, methodology has proposed for calculating the cost of production of dairy cattle atcost centers which are highlighted in business-processes in accordance with the physiological groups ofanimals. This technique allows you to reduce the cost of dairy products, as it will allow you to take intoaccount all factors affecting the value of production costsThe scientific significance of the research conducted in the article is to develop a set of theoreticaland practical recommendations on the organization and methodology of management accounting,analysis and control of costs in the agricultural organization. In particular, the proposed methodology forcalculating the cost of production of dairy farming in the cost centers, allows you to calculate the cost ofproduction at the level of variable costs for business processes of dairy farming, which creates a relevantinformation base for managers. The proposed methodology for organization of management accountingand analysis will allow each agricultural organization to choose a strategy for the development of planningand coordination of management decisions for a long period, provide owners and managers of alllevels of management with complete, prompt and reliable information on the activities of the agriculturalorganization.